Diversity of yeast poulations naturalised in Margaret River vineyards - Nugent, Elizabeth Fay (Curtin University, 2015)
The fermentation of grape must by the action of microbial species naturalised within the vineyard and/or winery environment, rather than the use of monoculture inoculation, is practiced within some sections of the wine industry. From a technological perspective this represents a retrograde step, and is driven by actual or perceived consumer demands for culturally and ethically responsible food products, and unique products with optimal and diversified sensory complexity. The vineyard environment houses a complex microbiota, potentially including naturalised yeast genotypes. The aim of this thesis is to identify the diversity of the naturalised yeast population in Margaret River vineyards, targeting the Saccharomycotina sub-phylum. In addition, it aims to improve existing methods for their identification and characterisation, and discuss the potential oenological implications of these species, and their role in naturalised fermentation. A diverse microbiota of fungal species capable of fermentation was identified within grape-derived samples sourced from Margaret River vineyards. The potential for pleasant and complex (from a sensory perspective) wines to be produced by these species is highlighted.However, the limits of current knowledge indicate there is still future research to be conducted. The application of appropriate barcodes for the culture-independent amplification of fungal species capable of fermentation was elucidated, and reinforces the validity of a two-gene approach. In addition, the modification of an appropriate plating regime for the application of culture-dependent analyses can now reduce the risk of cultivation bias in qualitative mucosal colony isolation from grape samples. The aims of this thesis were addressed in full, and the application of naturalised fermentation utilising diverse yeast populations naturalised in Margaret River vineyards, evaluated.